2022
DOI: 10.1186/s12870-022-03587-9
|View full text |Cite
|
Sign up to set email alerts
|

Small HSPs play an important role in crosstalk between HSF-HSP and ROS pathways in heat stress response through transcriptomic analysis in lilies (Lilium longiflorum)

Abstract: Background High temperature seriously limits the annual production of fresh cut lilies, which is one of the four major cut flowers in the global cut flower market. There were few transcriptomes focused on the gene expression of lilies under heat stress. In order to reveal the potential heat response patterns in bulbous plants and provide important genes for further genetic engineering techniques to improve thermotolerance of lily, RNA sequencing of lilies under heat treatments were conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The Food and Agriculture Organization Corporate Statistical Database (FAOSTAT) shows that cucumber is widely cultivated in the world and its cultivated area is next only to that of tomato and onion (FAOSTAT, 2022). HSP20 plays a crucial role in extreme temperatures (Peffer et al, 2019;Wu et al, 2019;Cui et al, 2021;Li et al, 2021;Sun et al, 2022;Zhou et al, 2022). Therefore, it is very necessary to study the roles of CsHSP20 genes under high temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The Food and Agriculture Organization Corporate Statistical Database (FAOSTAT) shows that cucumber is widely cultivated in the world and its cultivated area is next only to that of tomato and onion (FAOSTAT, 2022). HSP20 plays a crucial role in extreme temperatures (Peffer et al, 2019;Wu et al, 2019;Cui et al, 2021;Li et al, 2021;Sun et al, 2022;Zhou et al, 2022). Therefore, it is very necessary to study the roles of CsHSP20 genes under high temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Swollen leaf blades were oven dried at 80°C for 3 days. RWC was calculated as [(fresh weight -dry weight)/ (threshold weight -dry weight)] × 100 [14]. To estimate cell membrane damage, EL was measured using a conductivity meter (ST3100C, OHAUS Corporation, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Killed tissues were incubated in the shaker overnight at room temperature and nal conductivity was measured. The EL was calculated as (initial conductivity/ nal conductivity) × 100 [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, heat stress limits plant growth and even causes death under extreme conditions [13]. To counteract such detrimental effects, plants use numerous strategies to maintain cellular homeostasis for survival [14,15]. Transcriptomic analysis by RNA-seq in various plant species revealed that the genes involved in carbohydrate, lipid and protein metabolisms, oxidative stress responses, calcium signaling pathway and proline biosynthetic process were up-regulated.…”
Section: Introductionmentioning
confidence: 99%